Implementasi Algoritma Random Forest Untuk Mendiagnosis Kejadian Berulang (Kekambuhan) Pada Kanker Payudara Berbasis Web - Runi Hari Bagus Saputra; Roy Mubarok (CV. Multi Kreasi Media, 2022)
Cancer is the leading cause of death in developed countries and the second leading cause of death in developing countries. The Ministry of Health of the Republic of Indonesia (2019) stated that the incidence of cancer in Indonesia (population 136.2/100,000) was 8th in Southeast Asia and 23rd in Asia, according to data from the global cancer station in 2018. The highest incidence is in women, with breast cancer at 42.1 per 100,000 population and an average mortality rate of 17 per 100,000 population, followed by cervical cancer at 23.4 per 100,000 population, with an average mortality rate of 13.9 per 100,000 population. . With the assumption that breast cancer has disappeared from the patient's body, not many people know that breast cancer can recur. After the treatment process, usually only a few cancer cells survive. But at small doses, these cells can cause more serious problems. This disease can recur in the chest, chest, or other body parts, such as the bones and liver. To predict the recurrence of breast cancer, we need a technology-based system that can predict the recurrence of breast cancer. The algorithm used is Random Forest. It is a combination of all matching trees in one mode. This system is based on the PHP programming language and MySQL database as the storage medium. The PHP programming language is a programming language that is commonly used to create and develop websites and can be used in combination with HTML. MySQL, on the other hand, is the